COMPETENCE AND LEARNING OUTCOMES OF OLDER STUDENTS IN BASIC ENGLISH - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2017)
This research was conducted to describe the capability and learning outcomes of the older students of Primary Education Department in learning English as a basic course. The researcher wanted to see and explain the real image of their learning in their current ages. The participants of the study involved three older students of first year in Primary Education Department. Regarding the technique of collecting data, the researcher used three instruments i.e observation sheet, interview guide and test. The data were analysed qualitatively and quantitavively by using words and statistic descriptive. Results indicated that the competences of the two of three older students in English class were not effective any longer. Their learning outcomes also showed their weakness of absorbing input presented in learning process. On the other hand, another older student showed an improvement after giving strong effort.